The implication of gut microbiota in recovery from gastrointestinal surgery - Zheng, Zhipeng; Hu, Yingnan; Tang, Jingyi; Xu, Wenjun; Zhu, Weihan; Zhang, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Recovery from gastrointestinal (GI) surgery is often interrupted by the unpredictable occurrence of postoperative complications, including infections, anastomotic leak, GI dysmotility, malabsorption, cancer development, and cancer recurrence, in which the implication of gut microbiota is beginning to emerge. Gut microbiota can be imbalanced before surgery due to the underlying disease and its treatment. The immediate preparations for GI surgery, including fasting, mechanical bowel cleaning, and antibiotic intervention, disrupt gut microbiota. Surgical removal of GI segments also perturbs gut microbiota due to GI tract reconstruction and epithelial barrier destruction. In return, the altered gut microbiota contributes to the occurrence of postoperative complications. Therefore, understanding how to balance the gut microbiota during the perioperative period is important for surgeons. We aim to overview the current knowledge to investigate the role of gut microbiota in recovery from GI surgery, focusing on the crosstalk between gut microbiota and host in the pathogenesis of postoperative complications. A comprehensive understanding of the postoperative response of the GI tract to the altered gut microbiota provides valuable cues for surgeons to preserve the beneficial functions and suppress the adverse effects of gut microbiota, which will help to enhance recovery from GI surgery.